Aquarium as a tool for teaching Sciences al all grades levels - Seixas, Sónia (2007)
The aquarium are an excellent hands on teaching tool in the classroom, it offers students the opportunity to learn directly through experience. The first step is to choose the environmental and animals specifically for the objectives of teaching. Its possible creates environments of different places: seashore, corals reef, lakes, different rivers, etc. The most common tool for classrooms is an aquarium of freshwater. The material necessary depends on the environment chosen. The second step is set up the aquarium with all material necessary. Then is necessary select the gravel and decoration roots or stones. If is recommend for the environment chosen the species of plants to introduce. Finally the fishes and invertebrates must be introduced. The phase of set up allows the classroom understands the requirements of animals and plants, come from different environments. A several examples of different environments aquariums will be referred. After the aquarium is established the water parameters must be control, such as water temperature, pH, ammonia, nitrite and nitrate levels. Graph the information and looks to trends is an excellent way in such levels to explain a lot of concepts. The animals must be fed with appropriate food, this introduce the concept of food chain. The reproduction and behaviour of animals are also very important to understand zoology concepts. The reproduction and grow up of plants are also very important to understand botany. Is given some examples of done this in classroom.